COMPOSITION AND ABUNDANCE OF CRUSTACEA AND POLYCHAETA IN MANGROVE STANDS AT BULALO KWANDANG DISTRICT NORTH GORONTALO REGENCY - Katili, Abubakar Sidik; Utina, Ramli; Kurapu, Susantika (Proceedings of the International Conference on Green Technology; Vol 6 No 1 (2015): Proceeding of International Conference on Green Technology, 2020)
Background : The magnitude of the mangrove ecosystem can be seen from the number of organisms that live dependent on mangrove ecosystems. As we know that the mangrove ecosystem is where spawning and place foraging range of aquatic biota. Objectives: This study determine the composition and abundance of Crustacea and Polychaeta based Mangrove stands in the village of Bulalo Kwandang District of North Gorontalo regency. The research conducted over four months. The method used is survey method and techniques of data collection was done by using a sample square. The data were analyzed by descriptive quantitative. Results : The crustacea species which consists of 3 family, that is Portunidae, Sesarmidae, Ocypodidae, while the Polychaeta only one family that is Capitellidae family. At station 1 species which have the highest index of abundance that is Sesarma sp . Indv/m2 and 0.189 for species that have the lowest abundance index of 0.023 Indv/m2 Scylla serata . While at the station two species that have the highest abundance index Sesarma sp . of 0.188 Indv/m2 which has an index of abundance and low of Scylla serata the abundance index of 0.020 Indv/m2. The most abundance  species found in the Rhizophora sp stands. Where  species of the least discovered that the stand Avicenia sp .